2004
DOI: 10.1002/art.20035
|View full text |Cite
|
Sign up to set email alerts
|

Association of radiographic hand osteoarthritis with radiographic knee osteoarthritis after meniscectomy

Abstract: Objective. To evaluate the association between radiographic hand osteoarthritis (OA), a disease with marked heredity, and radiographic knee OA in patients treated with meniscectomy.Methods. We retrospectively identified 170 patients (mean age 54 years [range 33-87 years], 23% women) who had undergone isolated meniscectomy an average of 20 years earlier (range 17-22 years). Patients with cruciate ligament injury were excluded. All subjects were examined by standardized knee and hand radiography. Individual join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 27 publications
5
84
1
4
Order By: Relevance
“…Other risk factors thus need to be addressed. The contributing influence of heredity has been suggested by the association between radiographic OA of the hand and radiographic OA of the knee found after meniscectomy (13,36). We have previously demonstrated the impact of preexisting early-stage OA (8); in further support of this is the higher frequency of intraoperative cartilage changes seen in conjunction with the degenerative type of meniscal tear in the present study, consistent with previous findings (37,38).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other risk factors thus need to be addressed. The contributing influence of heredity has been suggested by the association between radiographic OA of the hand and radiographic OA of the knee found after meniscectomy (13,36). We have previously demonstrated the impact of preexisting early-stage OA (8); in further support of this is the higher frequency of intraoperative cartilage changes seen in conjunction with the degenerative type of meniscal tear in the present study, consistent with previous findings (37,38).…”
Section: Discussionsupporting
confidence: 92%
“…We have previously demonstrated an interaction between the endogenous risk factor heritable OA and exogenous OA risk in the form of meniscectomy (13), as well as the impact of the type of meniscal tear that may indicate preexisting early-stage knee OA (8). The present study was undertaken to evaluate the influence of additional risk factors for OA in the meniscectomized knee.…”
Section: Risk Factors For Symptomatic Knee Osteoarthritis Fifteen To mentioning
confidence: 91%
“…75 In the hand, the heritability of OA is more than 60%. 75 Previously, investigators 76 examined the association between hand OA and the risk of knee OA development after meniscectomy performed on average 20 years before study enrollment. The presence of hand OA was associated with a higher rate of knee OA development (OR ¼ 3.0; 95% CI ¼ 1.2, 7.5), thereby suggesting that knee OA development after meniscectomy may not be entirely due to joint trauma and that the patients who developed OA could have been genetically predisposed to develop the disease.…”
Section: Other Potential Risk Factorsmentioning
confidence: 99%
“…The presence of hand OA was associated with a higher rate of knee OA development (OR ¼ 3.0; 95% CI ¼ 1.2, 7.5), thereby suggesting that knee OA development after meniscectomy may not be entirely due to joint trauma and that the patients who developed OA could have been genetically predisposed to develop the disease. 76 Similarly, Valdes et al 77 researched the influence of genetic risk factors on total knee and total hip arthroplasty rates among individuals with or without a history of joint injury. Genetic factors contributed to the risk of total knee and hip arthroplasty nearly equally among individuals with or without a history of joint injury.…”
Section: Other Potential Risk Factorsmentioning
confidence: 99%
“…All subjects who have developed OA are probably affected by both genetics and environmental factors with individually distributed predominance. It has previously been reported that the risk of post-traumatic OA after a meniscal injury of the knee is strongly affected by a family history of OA, by the presence of generalized OA (like the nodal osteoarthritis of the hand), by obesity, and by sex [8][9][10]. Many subjects with OA in one joint have the disease at different stages in other joints.…”
Section: Pathogenesismentioning
confidence: 99%